Indonesian Cultural Diplomacy: Leveraging National Identity to Build a Positive Global Image - Saiman, Saiman (SEAN Institute, 2023)
As a country with high cultural diversity, Indonesia has significant potential to strengthen its position and influence in international relations through soft power. This study aims to analyze the strategy, implementation, and effectiveness of Indonesian cultural diplomacy in introducing national values, traditions, and character to the global community. The research employed qualitative methods with a descriptive approach, based on an analysis of literature, policy documents, and various cultural diplomacy activities such as arts festivals, cultural performances, culinary arts, and tourism promotion. The results indicate that Indonesian cultural diplomacy plays a crucial role in building a positive national image globally through the utilization of national identities such as art, culinary arts, education, film, digital media, and UNESCO intangible cultural heritage. These various programs have been effective in increasing global understanding and appreciation of Indonesia, although their implementation still faces obstacles such as lack of inter-agency coordination, budget constraints, suboptimal use of digital technology, low human resource competency, and the absence of an integrated cultural narrative. This study also found that solutions such as strengthening coordination, collaboration with the private sector and the diaspora, optimizing digital technology, increasing human resource capacity, and developing a national cultural narrative can increase the effectiveness of Indonesian cultural diplomacy. Overall, cultural diplomacy has proven to be a relevant and potent strategy for strengthening Indonesia's soft power and global image.